Case Report: The first record of Eustrongylides sp. infection in the Chinese alligator (Alligator sinensis) - Yujun Shuai; Yongkang Zhou; Yongkang Zhou; Pingsi Yi; Pingsi Yi; Jinhong Zhao; Jinhong Zhao (Frontiers in Veterinary Science)
Although digestive tract parasites are widely spread in wild or farmed crocodiles worldwide, only limited data are available on Eustrongylides sp. reported in crocodiles. The Chinese alligator (Alligator sinensis) is endemic to the Yangtze River in China, and only a few parasites have been reported to infect the Chinese alligator. In this study, a nematode was collected in the abdominal fascia of a captive deceased Chinese alligator. Cytochrome oxidase I (COI), internal transcribed spacer region (ITS) and partial small subunit DNA segments (18S) sequences were amplified to further confirm the genetic information of the species. The results showed that the nematode was attributed to the genus Eustrongylides. Overall, this is the first report of Eustrongylides sp. infected in the Chinese alligator, expanding the known host range of this nematode and contributing to a better understanding of its life cycle.